Innovation in smallholder farming in Africa: recent advances and recommendations: Proceedings of the International Workshop on Agricultural Innovation Systems in Africa (AISA) - Triomphe, Bernard; Waters-Bayer, Ann; Klerkx, Laurens; Schut, Marc; Cullen, Beth; Kamau, G; Le Borgne, Ewen (Centre de coopération internationale en recherche agronomique pour le développement, 2014)
In the wake of a series of recent international events and initiatives focusing on understanding and fostering innovation1, there is growing awareness and interest in applying and making sense of the Agricultural Innovation Systems (AIS) concepts and perspectives and what they offer for understanding and supporting innovation systems, processes and networks. This has particular relevance for African agriculture as it faces several challenges, such as increasing and intensifying food production in a sustainable way and nourishing its fast-growing population, adapting to the consequences of climate change, and finding its rightful place in an increasingly global and complex international scene. Several initiatives and programmes seeking answers to these questions jointly organised a series of events during a Week on Agricultural Innovation in Africa (WAIA) held in Nairobi, Kenya, on 25–31 May 2013, of which the international workshop on Agricultural Innovation Systems in Africa (AISA) on 29–31 May was a major part. Another key event during this week, was the Eastern African Farmer Innovation Fair (EAFIF) held on 28–29 May, which was linked to AISA.